Estimation of carbon stock and economic valuation of mangrove ecosystem in Ngurah Rai Grand Forest Park, Bali, Indonesia - ARIFAH DINDA LESTARI; MUFTI PETALA PATRIA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Lestari AD, Patria MP. 2025. Estimation of carbon stock and economic valuation of mangrove ecosystem in Ngurah Rai Grand Forest Park, Bali, Indonesia. Biodiversitas 26: 2821-2831. Ngurah Rai Grand Forest Park (GFP), Bali, is considered one of Indonesia’s successful examples of mangrove forest restoration, yet it remains ecologically vulnerable due to persistent anthropogenic pressures. An essential component of mangrove restoration is ecosystem monitoring, which includes both ecological assessments and economic valuation to determine carbon sequestration potential. The mangrove ecosystem in Ngurah Rai GFP provides tangible ecological, physical, and economic benefits to the local community, necessitating comprehensive evaluation to support long-term sustainability. This study aimed to assess the economic value of mangroves and estimate their carbon sequestration potential to better understand their contribution to climate change mitigation. Fieldwork was conducted from March to September 2024. Carbon sequestration was estimated using a non-destructive allometric model to measure mangrove tree biomass and sediment carbon content was analyzed using the Loss on Ignition (LOI) method. The Total Economic Value (TEV) of the mangrove ecosystem was estimated by incorporating direct use values (ecotourism, fisheries, and processed mangrove products); indirect use values (carbon sequestration, coastal protection, and ecological functions such as spawning, feeding, and nursery grounds); option values (biodiversity benefits); existence values (willingness to pay); and bequest values. The results revealed that the average carbon sequestration potential in Ngurah Rai GFP is 1,742.08 tons CO?/ha/year. The Direct Use Value (DUV) was IDR 675,615,035,500/year; the Indirect Use Value (IUV) was IDR 862,383,525,618/year; and the Existence Value (EV) was IDR 185,158,788,000/year. The Option Value (OV), derived from biodiversity benefits, was IDR 722,958,245/year, while the Bequest Value was estimated at IDR 67,561,503,550/year. The total TEV of the mangrove ecosystem in Ngurah Rai GFP was IDR 1,791,441,810,913/year, equivalent to approximately USD 107,918,182/year.